Preliminary study of an automatic detection capsule system for gastric occult blood. (1st January 2013) - Liu, Hongying; Qiao, Panpan; Wu, Xueli; Zhu, Lan; Pi, Xitian; Zheng, Xiaolin
Based on capsule endoscopy and Occult Blood (OB) detection theory, an automatic detection capsule system for Gastric Occult Blood (GOB) was proposed. This system utilised the non-invasive deglutible capsule to automatically identify the GOB information and transmitted the detection result to the external device which could display the detection result and identify the OB status with a particular algorithm. Subjects or doctors could discriminate whether OB existed by observing the external device. This paper designed the automatic detection capsule of GOB and the detecting sensor based on collaurum immune theory. We did in vitro experiments to testify the system and acquired the detecting result image information. Experimental results indicated that the effective detection concentration range of the OB sensor was 6–1800 μg/ml. With simplicity and reliability, this system provides a new idea for the screening of early stage gastric cancer.